Public support for second look sentencing: is there a Shawshank redemption effect? - Hannan, Kellie R. (Criminology & public policy, 2023)
Research Summary Washington, DC has implemented second look sentencing. After serving a minimum of 15 years in prison, those convicted of a serious offense committed while under the age of 25 years can petition a judge to take a "second look" and potentially release them from incarceration. To examine both global and specific support for second look sentencing, we embedded experiments in a 2021 MTurk survey and in a follow-up 2022 YouGov survey. Two key findings emerged. First, regardless of whether a crime was committed under 18 years or under 25 years of age, a majority of the public supported second look sentencing. Opposition to the policy was low, even for petitioners convicted of murder. Second, as revealed by vignette ratings, respondents were more likely to support release when a petitioner "signaled" their reform (e.g., completed a rehabilitation program, received a recommendation from the warden) and had the support of the victim (or their family). Policy Implications The critique of mass imprisonment has broadened from a focus on the level of incarceration to the inordinate length of sentences being served by some prisoners. Policies are being proposed to reconsider these long sentences and to provide opportunities for earned release. Second look sentencing in DC is one of these reforms. Our research suggests that many members of the public believe in a "Shawshank redemption" effect - that those committing serious crimes as a teenager or young adult can mature into a "different person" and warrant a second look, with the possibility of early release if they have earned it. A key issue is likely to be how much weight is accorded to the preference of victims or their families in any release decision.